Memaknakan Pengalaman Traumatis Kekerasan: Hannah Arendt dan Viktor Frankl - Lengkong, Felix (Jurnal Etika Respons, 2009)
Holocaust is such a traumatizing event, not only to those who had a direct contact with it such as Hannah Arendt and Viktor Frankl, but also to many people who have indirectly got to know about it through reading or watching Holocaust movies. Assuming that both Hannah Arendt and Viktor Frankl were somehow affected by such a traumatic experience, this article traces out such an effect in the works and writings of those celebrated thinkers. From the perspective personality psychopathological symptoms â traced in the life history of both â it concludes that there were no traces of posttraumatic stress in the life of both thinkers. Seemingly their positive cognitive processes took them from posttraumatic stress control. Instead of succumbing to despair, in line with Franklâs theory â they found meaning in the suffering.